Current Trends in Pickering Emulsions: Particle Morphology and Applications. (April 2020) - Gonzalez Ortiz, Danae; Pochat-Bohatier, Celine; Cambedouzou, Julien; Bechelany, Mikhael; Miele, Philippe
Graphical abstract: Highlights: Overview of Pickering emulsions and their applications is reported here. In pickering emulsions, solid particles are located at the liquid–liquid interface. Their morphology influences the droplets lifetime. Nanoparticles (NPs) morphology plays as well a crucial role in their applications. Influence of NPs morphology on the emulsion type and stability is highlighted. Abstract: In recent years, Pickering emulsions and their applications have attracted a great deal of attention due to their special features, which include easy preparation and enhanced stability. In contrast to classical emulsions, in Pickering emulsions, solid microparticles or nanoparticles that localize at the interface between liquids are used as stabilizers, instead of surfactants, to enhance the droplet lifetime. Furthermore, Pickering emulsions show higher stability, lower toxicity, and stimuli-responsiveness, compared with emulsions that are stabilized by surfactants. Therefore, they can be considered attractive components for various uses, such as photocatalysis and the preparation of new materials. Moreover, the nanoparticle morphology strongly influences Pickering emulsion stability as well as the potential utilization of such emulsions. Here, we review recent findings concerning Pickering emulsions, with a particular focus on how the nanoparticles morphology (i.e., cube, ellipsoid, nanosheet, sphere, cylinder, rod, peanut) influences the type and stability of such emulsions, and their current applications in different fields such as antibacterial activity, protein recognition, catalysis, photocatalysis, and water purification.